Improved processability of electrospun poly[(R)-3-hydroxybutyric acid] through blending with medium-chain length poly(3-hydroxyalkanoates) produced by pseudomonas putida from oleic acid - Azari, P.; Yahya, R.; Wong, C.S.; Gan, S.N. (Maney Publishing, 2014)
Polyhydroxyalkanoates are bacterial biopolyesters having good biocompatibility and biodegradability. Poly[(R)-3-hydroxybutyric acid] is the least expensive/costly and most easily available member of this family. However, poly[(R)-3-hydroxybutyric acid] is very brittle because of its high crystallinity. Its poor processability poses limitations on its application. Blending of this material with another amorphous flexible polymer has been a common practice. In this research, we have improved the properties of poly[(R)-3-hydroxybutyric acid] through blending with a palm oil-based medium-chain length polyhydroxyalkanoate. Solution blending was carried out at four different ratios to produce electrospun fibres. As expected, the addition of medium-chain length polyhydroxyalkanoate has reduced the brittleness of poly[(R)-3-hydroxybutyric acid], through reducing the crystallinity. In addition, it has enabled the reduction of the diameter of the electrospun fibres and shifted it from micrometre towards nanometres, which can improve its porosity and permeability to make it a potential material in biomedical applications.